Electron contamination for 6 MV photon beams from an Elekta linac: Monte Carlo simulation - Choirul Anam; Djarwani S Soejoko; Freddy Haryanto; Sitti Yani; Geoff Dougherty (Journal of Physics and Its Applications, 2020)
In external beam radiotherapy, the photons from a linear accelerator (linac) machine undergo multiple interactions, not only in the patient but also in the linac head and the air column between the linac head and the patient. Electrons are released from these interactions and contaminate the beams. The current study evaluates electron contamination for 6 MV photon beams from an Elekta linac using Monte Carlo simulation. The linac head was simulated by the BEAMnrc code and the absorbed dose in a phantom was calculated using the DOSXYZnrc code. The parameters of the initial electron beams on the target, such as mean energy and radial intensity distribution, were determined by matching the calculated dose distributions with the measured dose (at 10 x 10 cm2 field size and 90 cm source-skin distance). The central axis depth-dose curves of electron contamination were calculated for various field sizes from 5 x 5 cm2 to 40 x 40 cm2. We investigated the components that generated the electron contamination for a field size of 10 x 10 cm2. The optimal initial electron beam energy was 6.3 MeV with a full-width half maximum (FWHM) of the radial intensity distribution of 1.0 mm. These parameters were found to be in good agreement with the measured data. Electron contamination increased as the field size increased. At a depth of 1.0 mm and field sizes of 5 x 5, 10 x 10, 20 x 20, 30 x 30, and 40 x 40 cm2, the doses from electron contamination were 3.71, 5.19, 14.39, 18.97 and 20.89 %, respectively. Electron contamination decreased with increased depth. At a depth of 15 mm, the electron contamination was about 1 %. It was mainly generated in the air column between the linac head and the phantom (3.65 %), the mirror (0.99 %), and the flattening filter (0.59 %) (for the depth of 1.0 mm and the field size of 10 x 10 cm2).